2010
DOI: 10.1186/1752-0509-4-36
|View full text |Cite
|
Sign up to set email alerts
|

Building and analyzing protein interactome networks by cross-species comparisons

Abstract: BackgroundA genomic catalogue of protein-protein interactions is a rich source of information, particularly for exploring the relationships between proteins. Numerous systems-wide and small-scale experiments have been conducted to identify interactions; however, our knowledge of all interactions for any one species is incomplete, and alternative means to expand these network maps is needed. We therefore took a comparative biology approach to predict protein-protein interactions across five species (human, mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 48 publications
0
63
0
1
Order By: Relevance
“…Such cross-species studies offer the opportunity to identify networks not easily identifiable in individual species datasets (73). Additionally, the use of multiple RNAi screens could overcome the reported high false-positive rate in mammalian RNAi screens due to off-target affects (74).…”
Section: Discussionmentioning
confidence: 99%
“…Such cross-species studies offer the opportunity to identify networks not easily identifiable in individual species datasets (73). Additionally, the use of multiple RNAi screens could overcome the reported high false-positive rate in mammalian RNAi screens due to off-target affects (74).…”
Section: Discussionmentioning
confidence: 99%
“…A line is assigned between connected evocations. The net-work is displayed in a graph, which presents the spatially strongest co-occurrences between pairs of elements thus reflecting the most intensive relations between the phrases (Coronges et al, 2007;Wiles et al, 2010). The most important nodes (circles) are by nature the hubs of the network.…”
Section: Similarities (Co-occurrence) Methodsmentioning
confidence: 99%
“…They found that the homology transfers are only accurate at high levels of sequence identity, and it is more reliable for protein pairs from the same species than for two protein pairs from different organisms (Mika and Rost 2006). Likewise, Wiles et al, (2010) have developed a scoring schema to assess the confidence of interologs prediction. They have predicted protein interactions across five species (human, mouse, fly, worm, and yeast) based on available experimental evidence and conservation across species (Wiles et al, 2010).…”
Section: Interologsmentioning
confidence: 99%
“…Likewise, Wiles et al, (2010) have developed a scoring schema to assess the confidence of interologs prediction. They have predicted protein interactions across five species (human, mouse, fly, worm, and yeast) based on available experimental evidence and conservation across species (Wiles et al, 2010). Also, they developed the Interolog Finder (URL: http://www.interologfinder.org) to provide access to these data.…”
Section: Interologsmentioning
confidence: 99%